2015
DOI: 10.1021/acs.nanolett.5b01929
|View full text |Cite
|
Sign up to set email alerts
|

Optical Epitaxial Growth of Gold Nanoparticle Arrays

Abstract: We use an optical analogue of epitaxial growth to assemble gold nanoparticles into 2D arrays. Particles are attracted to a growth template via optical forces and interact through optical binding. Competition between effects determines the final particle arrangements. We use a Monte Carlo model to design a template that favors growth of hexagonal particle arrays. We experimentally demonstrate growth of a highly stable array of 50 gold particles with 200 nm diameter, spaced by 1.1 μm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…It is intriguing that the scattering directions of the particles can be varied by adding salt, and thus the patterns of the assemblies are different from the situation without salt ( Figure 3 B). In Figure 3 C, Huang et al have showed the optical epitaxial growth of Au nanoparticle (200 nm in diameter) arrays [ 70 ]. Optical forces and optical binding make particles attach to the template, resulting in various particle arrangements.…”
Section: Light-controlled Swarming and Assembly Of Cpsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is intriguing that the scattering directions of the particles can be varied by adding salt, and thus the patterns of the assemblies are different from the situation without salt ( Figure 3 B). In Figure 3 C, Huang et al have showed the optical epitaxial growth of Au nanoparticle (200 nm in diameter) arrays [ 70 ]. Optical forces and optical binding make particles attach to the template, resulting in various particle arrangements.…”
Section: Light-controlled Swarming and Assembly Of Cpsmentioning
confidence: 99%
“… Optical forces-maneuvered assembly of colloidal particles (CPs). ( A ) Schematic illustration of manipulating metal CPs with optical forces (reproduced from [ 68 ]); ( B ) assembly of polystyrene (PS) nanoparticles induced by directional and homogeneous light scattering with or without salt (reproduced from [ 69 ]); ( C ) optical epitaxial growth of Au nanoparticle arrays (reproduced from [ 70 ]); ( D ) light-assisted and templated self-assembly of PS nanoparticles on a photonic crystal slab (reproduced from [ 71 ]). …”
Section: Figurementioning
confidence: 99%
“…Light-assisted self-assembly of gold nanoparticle chains has been reported [ 85 ]. Optical tweezers patterned highly stable 2D array of Au nanoparticles (diameter: 200 nm) was shown in Figure 6 a [ 86 ]. The Au nanoparticles can be precisely patterned with a uniform space of 1.1 μm.…”
Section: Controlled Swarming and Assembly Of Artificial Micromotormentioning
confidence: 99%
“… Light induced swarming and assembly of micro/nanoparticles. ( a ) Optical analogue of epitaxial growth to assemble gold nanoparticles (reproduced from [ 86 ]). ( b ) Schooling behavior of light-powered AgCl micromotors (reproduced from [ 87 ]).…”
Section: Figurementioning
confidence: 99%
“…Bio-mediated synthesis of metal and inorganic compound based NPs employing extracts both from single and multi-cellular organisms has been considered as an enticing approach worldwide 911 . Recently available nano-sized drug materials, the so-called self-assembled metal NPs, synthesized by employing plant or microbial extract, have elicited enormous interest in nano-therapeutics 1216 .…”
Section: Introductionmentioning
confidence: 99%